Study of fan films about video games as a tool for appropriation of the official canon - Paredes-Otero, Guillermo (2022)
This research aims to fill the existing void in academic research on fan films based on video games as a transmedia expansion strategy. The objective is to analyze how video game followers apply the principles of transmedia narrative when appropriating the fictional world of video games in their fan films and whether they respect or subvert them. The methodology is descriptive and based on a content analysis of 89 films based on current video game sagas created by fans and stored in fan film repositories and on YouTube; it delves into the characters, the events, the duration, and the realism of the footage as compared to the official canon. The results demonstrate the interest in creating original experiences but respecting the interactive franchise with short films that fill in the plot gaps while expanding the game universe with new characters and events. The study reveals the professionalism behind these productions, which goes beyond isolated and amateur practices. It also establishes a profile of the prototypical audiovisual production for future studies.